The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1988
DOI: 10.2307/2061290
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment of children from single-parent families: Differences by exposure, gender, and race

Abstract: This article examines the effect of living in a single-parent family on educational attainment by gender and race. According to household production theory, the reduction in parental resources for human capital investment in children living in a single-parent family should lower their educational attainment. Using matched mother-daughter and mother-son samples from the National Longitudinal Surveys, we constructed precise measures of the age and length of time a child lived in a single-parent family. Empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
1
5

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(156 citation statements)
references
References 19 publications
6
142
1
5
Order By: Relevance
“…See, for example, Astone and McLanahan (1991), Hogan and Kitagawa (1985), Krein andBeller (1988), andSandefur (1994). Manski, et al (1992) used data from the National Longitudinal Study of Youth (NLSY) initiated in 1979 to estimate the effect on high school graduation of living in an intact two-parent home during 13 adolescence.…”
Section: An Illustrative Application To a Quasi-experimentsmentioning
confidence: 99%
“…See, for example, Astone and McLanahan (1991), Hogan and Kitagawa (1985), Krein andBeller (1988), andSandefur (1994). Manski, et al (1992) used data from the National Longitudinal Study of Youth (NLSY) initiated in 1979 to estimate the effect on high school graduation of living in an intact two-parent home during 13 adolescence.…”
Section: An Illustrative Application To a Quasi-experimentsmentioning
confidence: 99%
“…There is some early United States research supporting the "early is worse" proposition from the 1980s (Krein 1986;Krein and Beller 1988). Krein and Beller find the effect on years of completed schooling is strongest during early childhood, increases with amount of exposure and is larger for boys than girls.…”
mentioning
confidence: 99%
“…Research indicates that low levels of education in specific populations are correlated with factors such as socio-economic status (Eagle, 1989), ethnicity (Gang & Zimmermann, 2000), geography (Garner & Raudenbush, 1991), and parental educational attainment (Krein & Beller, 1988). Several studies have indicated that low educational attainment levels among Indigenous peoples in Canada are also tied to colonialism (Miller, 1996).…”
Section: Indigenous Educational Attainment In Canadamentioning
confidence: 99%
“…Much of the research indicates that success leads to success. Parental educational attainment is highly correlated with children's success (see Krein & Beller, 1988). Improving attainment in each generation will build greater successes in the next.…”
Section: Policy For Moving Educational Attainment Forwardmentioning
confidence: 99%